International parental child abduction in the Malaysian legal context: issues and the way forward - Hamid, Abdul Ghafur@Khin Maung Sein; Kamaruddin, Zaleha (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
The number of international parental child abduction cases is gradually increasing and the problem has now become a global phenomenon. The worrying situation is that the problem in question is extremely difficult to resolve due to conflicting substantive and procedural laws in various countries. The 1980 Child Abduction Convention is an attempt to address the problem by means of an automatic return mechanism of the abducted child to his country of habitual residence. However, a Malaysian parent would not have that privilege as Malaysia is not a party to the Convention. The primary focus of the present work is to examine whether Malaysia has adequate legal and procedural framework to address the issue of cross-border parental child abduction. The present work makes a thorough analysis of the dual legal system of Malaysia, namely both the civil law and Islamic law streams when dealing with child custody and parental child abduction and assesses in-coming and out-going international parental child abduction cases decided by the Malaysian courts. The article finds that although in the long run, Malaysia should accede to the Child Abduction Convention, there are legitimate concerns on the part of stakeholders and on the fact that the opinion on the ground is against the accession. The article concludes that in the meantime, section 52 of the Child Act 2001 should be amended to strengthen the legal regime regulating parental child abduction in Malaysia.